2021
DOI: 10.1002/jcla.24034
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic protocol for hereditary spherocytosis‐2021 update

Abstract: Hereditary spherocytosis (HS) is a hereditary hemolytic anemia caused by the mutations in the genes encoding erythrocyte membrane proteins and is mostly inherited in an autosomal dominant manner. 1-3 HS is classified into four types according to the severity of the disease: trait, mild, moderate, and severe. Commonly, there is heterogeneity of the clinical manifestations in patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 52 publications
3
33
0
1
Order By: Relevance
“…NGS is an extremely important test in the molecular diagnosis of HS in clinical practice, including targeted exome sequencing (TES) and whole exome sequencing (WES) (16). Previous studies have demonstrated the usefulness of the targeted NGS methods in investigating the causal gene variants in patients with HS (17,18). In the present study, we found six novel gene mutations in children with HS.…”
Section: Discussionsupporting
confidence: 49%
“…NGS is an extremely important test in the molecular diagnosis of HS in clinical practice, including targeted exome sequencing (TES) and whole exome sequencing (WES) (16). Previous studies have demonstrated the usefulness of the targeted NGS methods in investigating the causal gene variants in patients with HS (17,18). In the present study, we found six novel gene mutations in children with HS.…”
Section: Discussionsupporting
confidence: 49%
“…The typical clinical manifestations of HS are intermittent hemolytic anemia, splenomegaly, and increased bilirubin (mostly indirect bilirubin). A peripheral blood smear will show increased spherocytosis, and laboratory tests will show an increased osmotic fragility (OF) value for the RBC ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Diagnosis is usually made by evaluation of clinical and hematological findings and family history. Genetic analysis for the specific protein mutations can be performed however it is not essential for the diagnosis generally (34)(35)(36)(37). Folic acid supplementation is recommended in these patients with a dose of 1 mg/day.…”
Section: Membranopathiesmentioning
confidence: 99%